Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Keaktifan Dan Kedisiplinan Belajar Siswa Pada Mata Pelajaran Ips Kelas IX A Smp Muhammadiyah 2 SimoTahun Ajaran 2016/2017 - Wulandari, Catur, Dra. Titik Asmawati, SE, M.Si (2017)
This research aims to enhance the activity and discipline students' learning model Problem Based Learning. This research is a claasroom action research conducted in two cycles. The subjects were teachers who provide action recipients are students of class IX A SMP Muhammadiyah 2 Simo totaling 26 students. Data collection methods used were observation, interviews, field notes and documentation. Data analysis technique used is the process of data analysis, data presentation, and data verification. The results showed an increase activeness and discipline students in social studies. Students' learning activeness can be seen from the indicators, namely: 1) Participate in carrying out the ask of learning before action 80,76% and the at the end of the action 100%, 2) Engage in problem solving as much as 7,69% before treatment and at the end of the action as much 84,61%, 3) To ask another student or the teacher if it does not understand the problems faced before action as much as 15,38% and at the end of the action as much as 80,76%, 4) Trying to find a variety of information needed to solve the problem before the action as much as 11,53% and at the end of the action becomes 76,92%, 5) Conducting group discussions in accordance with the instructions of teachers before actions 76,92%, 6) Assessing the ability of himself and the results obtained prior to the action as much as 19,21% and at the end of the actions as much as 69,23%, 7) Train yourself in solving problems or similar problems before the action as much as 26,92% and in final action becomes 73,07%, 8) Opportunity use or apply what has been gainedin completing a task or problem faces prior to the action as 23,07% and at the end of the action as much as 76,92%. Students learn discipline can be seen from the indicators, namely 1) diligently and regularly studied before action as much as 34,61% and at the end of the action becomes 76,92%, 2) Adherence to the duties subject is before the action as much as 42,30% and at the end action be 92,30%. Thus concluded that the use of Problem Based Learning model of learning can enhance the activity and discipline of student learning in social studies class IX A students SMP Muhammadiyah 2 Simo.